Cogeneration power stations. - Suyunova M.B (Genius Journals, 2024)
In this article, we explore the basic concept of cogeneration power plants, their operating principles, and the main benefits they provide in terms of energy efficiency and environmental sustainability
Keywords: Power Plants; Energy; Heat; Environment